ANALYSIS OF SEGMENTATION AND TARGETING OF JEANS IN JAKARTA - Aprilian, Dian Rahayu; Bimo, Charisma Aryo; Pakpahan, Arnolt Kristian (Dynamic Management Journal, 2024)
Jeans are a significant part of the global apparel industry, with a vast market. This research aims to analyze how the jeans segmentation is formed and who exactly is the target market. The population in this study were all groups who wear jeans in Jakarta. The technique used in determining the sample was purposive sampling with a total of 161 people. The type of research used in this research is descriptive research using the hierarchical procedure method to search for segmentation. This analysis aims to see whether there are significant differences between each cluster or group formed. Then, in searching for target markets, this research uses a non-hierarchical procedure method. From the results of the analysis, 2 clusters were formed where the 2nd cluster was selected as the target market. It is hoped that the results of this analysis can provide input to jeans business actors to be able to attract more potential consumers and accurately. This study employs sentiment analysis to delve into the preferences and opinions of jeans users in Jakarta, offering fresh insights for businesses to develop more effective marketing strategies and understand market trends, consumer preferences, and growth potential.